Making of a native orientalist: latent orientalism in confessions of an old boy: The Dato’ Hamid Adventures - Ahmad Thamrini Fadzlin B. Syed Mohamed,; Noraini Bt. Md. Yusof,; Ruzy Suliza Hashim, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2010)
The purpose of this paper is to examine the sustaining effects of colonialism perpetuated in one of Malaysia‟s premier schools, The Malay College Kuala Kangsar (MCKK), as discerned through Kam Raslan‟s Confessions of an Old Boy: The Dato‟ Hamid Adventures (2007). By highlighting that culture is a learned behaviour and man-made, this paper argues that a cultural programming process took place within the education system implemented in MCKK which was inherently an ideology transference mechanism appropriated by the British on the Malays. By blending the basic principle of computing process together with Edward Said‟s idea on the latent form of Orientalism, the cultural programming model makes overt certain colonial culture and ideology instilled through MCKK‟s form and function in serving the colonial interest. Hence, through the analysis of novel and historical accounts on the development of MCKK, we show that the British had surreptitiously transferred their culture and ideology as discerned through the character, Dato‟ Hamid.